Student Experiences in First Year Engineering Classrooms - Exploring Issues of Gender in an Australian Program - Lloyd, Natalie; Syzmakowski, J. (Engineers Media Pty Ltd., 2017)
The 2016 cohort of first year engineering undergraduates, arranged in groups of about 20, consisted of eight groups with at least one-third females, five groups with one or two females and sixteen male-only groups. The groups had a common timetable for all lectures, workshops, tutorials and laboratories for eight core units. The hypothesis was groups with a higher proportion of females would enable female students to self-select small groups of gender parity or majority for teamwork activities in classrooms. Furthermore, these small groups would be microenvironments supportive of female verbal participation and engagement whilst minimising discrimination. Qualitative and quantitative data collection from classroom observations preceded quantitative data collection using a survey instrument and student and learning analytics data. Whilst acknowledging the limitations of the research and complexity of interacting factors, including those from pre-university that were outside the scope of the research, the strategy of group allocation piloted in 2016 did create microenvironments of gender parity or majority. Classroom observations indicate female students engaged. Further research to investigate the disparity of threat to challenge ratios reported by male and female students is recommended.